Komitmen Takmir Masjid Jogokariyan untuk Meningkatkan Perkonomian Umat melalui Pasar Rakyat Jogokariyan (PRJ) - Suhartini, Tien; Hasrudin, Hasrudin (EKOBIS, 2025)
Since the government of the Republic of Indonesia imposed large-scale of social distancing (pembatasan sosial berskala besar or PSBB) in early 2020, economic actors have had difficulty maintaining their businesses. The impact of the Covid-19 pandemic has also been felt by MSMEs (micro, small, and medium enterprises) of the Masjid Jogokariyan congregation (jamaah). In order to care for the jamaah and to improve the economic level of the jamaah at the Masjid Jogokariyan, finally the takmir (manager) took the initiative to create the Pasar Rakyat Jogokariyan (PRJ) which means Jogokariyan People's Market program. This PRJ opens up opportunities for new comer business actors or old players affected by Covid-19. Takmir began using digital platforms and marketing mix strategies. This study used a qualitative method with a phenomenological approach, collected data using in-depth interviews, observations, and documentation. The data analysis used Creswell's phenomenological analysis. This study aims to determine the policies of the Masjid Jogokariyan administrators in managing the PRJ Program both from the perspective of human resource management (HRM) and marketing management. We managed to meet 27 people and provide sufficient information for us to use as informants. The key informant was the head of the Masjid Jogokariyan administrators. Through him, we were directed to obtain other information from masjid jamaah, tourists, and MSME owners involved in the PRJ program. PRJ at that time was an alternative program to overcome economic problems experienced by residents or jamaah of the Masjid Jogokariyan. Over time, and the economy has started to return to normal, PRJ has now changed to the pasar Ramadhan Jogokariyan (Jogokariyan Ramadhan Market) which of course only exists during the month of Ramadan. Other masjids can adapt and modify programs like this to overcome similar problems. Keywords: Takmir Masjid, Masjid Jogokariyan, People's Market, Digital Marketing, Masjid Administrators' Policies.